Embodied Pathways in Early Arabic Phoneme Acquisition: A Phenomenological Study in a Non‑Formal Religious Context - Achmad Fudhaili; Muhammad Ivang Rizaldi; Alif Alvian Mawardi Hamid (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2026)
This study investigates the acquisition of Arabic phonemes in early childhood within a non‑formal religious learning context, emphasising phonological development as an embodied, developmental, and socially mediated process. Moving beyond segment-centred and outcome‑oriented perspectives, the study employs a qualitative phenomenological approach to explore young learners’ lived experiences as they perceive, articulate, and internalise Arabic phonemes that are typologically distant from their first language. The research was conducted in a rumah Qur’an in Jakarta, Indonesia, involving three children aged four to six at different instructional levels and one experienced instructor. Data were collected through non‑participant observation, semi‑structured interviews, and document analysis, and were analysed inductively using phenomenological thematic procedures. The findings indicate that early Arabic phoneme acquisition begins with holistic sensorimotor experiences rather than abstract phonological categories, with phonemes initially understood as bodily articulatory actions. Consistent substitution patterns emerge as adaptive developmental strategies shaped by first‑language phonology. Repetitive Qur’anic recitation supports the proceduralization of embodied articulatory routines, while teacher‑mediated multimodal scaffolding facilitates phonemic differentiation through perceptual and motor reorganisation. The study concludes that early Arabic phonological development is best explained through an integrative model combining embodied cognition, Natural Phonology, the Speech Learning Model, and sociocultural theory, highlighting pedagogical value of religious education.